If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(2a + 4) = 6a + -4 Reorder the terms: 5(4 + 2a) = 6a + -4 (4 * 5 + 2a * 5) = 6a + -4 (20 + 10a) = 6a + -4 Reorder the terms: 20 + 10a = -4 + 6a Solving 20 + 10a = -4 + 6a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-6a' to each side of the equation. 20 + 10a + -6a = -4 + 6a + -6a Combine like terms: 10a + -6a = 4a 20 + 4a = -4 + 6a + -6a Combine like terms: 6a + -6a = 0 20 + 4a = -4 + 0 20 + 4a = -4 Add '-20' to each side of the equation. 20 + -20 + 4a = -4 + -20 Combine like terms: 20 + -20 = 0 0 + 4a = -4 + -20 4a = -4 + -20 Combine like terms: -4 + -20 = -24 4a = -24 Divide each side by '4'. a = -6 Simplifying a = -6
| 1.2m=.6 | | (x^2-5x-3)(x^2-5x-5)=3 | | -x+6x-9=0 | | 2y=-10x+4 | | -7=9x+16-10 | | 2(x+p)=3(6p-x) | | 9k-3k=30 | | 3y+4=y+18 | | -44-1x=28-4x | | x-7.1=-6.2 | | -(3y+1)-(-2y-7)=2 | | 96-2x=43x+16 | | 7(7x-3)+10x= | | 2x+80=158 | | 5p-3=32 | | 3x=3x+2 | | x=.4+(-.2y) | | B-2+6B=27 | | 3x/4=6 | | 6x-11x+4=0 | | 13x^2+1-[7(x^2-8)+5]= | | 6x^7-18x^4+24x^6= | | 6+2y-2=9y+13-6y | | 14(t-3)+4t=6(3t+3)-10 | | 2x-5=x+7+2x | | 5fg+g^2=0 | | 2x+-.5=-.75 | | 5fg+g^2=03 | | 7x+15=29 | | 7a+21b=35 | | 3*4=10 | | 5x+7=25-x |